2021
DOI: 10.3390/antibiotics10020114
|View full text |Cite
|
Sign up to set email alerts
|

Think Twice before Prescribing Antibiotics for That Swollen Knee: The Influence of Antibiotics on the Diagnosis of Periprosthetic Joint Infection

Abstract: Periprosthetic joint infection (PJI) is a rare but devastating complication after total joint arthroplasty. An estimated 7–12% of patients have negative cultures despite clear clinical evidence of infection. One oft-cited reason for this occurrence is the administration of antibiotics in the weeks prior to obtaining cultures. This article reviews the influence of antibiotics on the diagnosis of PJI. Specifically, we examine the effect of prophylactic and therapeutic antibiotic administration on the diagnostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 95 publications
(93 reference statements)
2
11
0
1
Order By: Relevance
“…Moreover, higher rates of polymicrobial infections in FRI have been described comparing different sampling protocols (25% and 36%, respectively) [ 12 ]. The present rate of culture-negative PJIs (13.6%) was similar to previous reports indicating a proportion of 5% to 12% [ 13 , 14 ]. Differences in reported polymicrobial and culture-negative PJI rates might be due to local epidemiology and different diagnostic criteria used for PJI and FRI as well as previous antibiotic treatment, which decreases microbial diagnostic yield [ 15 , 16 ].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, higher rates of polymicrobial infections in FRI have been described comparing different sampling protocols (25% and 36%, respectively) [ 12 ]. The present rate of culture-negative PJIs (13.6%) was similar to previous reports indicating a proportion of 5% to 12% [ 13 , 14 ]. Differences in reported polymicrobial and culture-negative PJI rates might be due to local epidemiology and different diagnostic criteria used for PJI and FRI as well as previous antibiotic treatment, which decreases microbial diagnostic yield [ 15 , 16 ].…”
Section: Discussionsupporting
confidence: 91%
“…8,11,15 Furthermore, human studies have found that inappropriate antibiotic therapy can render many pathogens viable but non-culturable, thus yielding a falsely negative culture. 5,[20][21][22] However, administration of perioperative prophylactic antibiotics has been shown to not have an effect on culture results in several studies. [21][22][23] It remains debatable whether culturing synovial fluid or synovial membrane improves the diagnostic yield of infected joints.…”
Section: Discussionmentioning
confidence: 99%
“…5,[20][21][22] However, administration of perioperative prophylactic antibiotics has been shown to not have an effect on culture results in several studies. [21][22][23] It remains debatable whether culturing synovial fluid or synovial membrane improves the diagnostic yield of infected joints. Studies in dogs, horses and humans with SA have found synovial fluid culture to be significantly more reliable in yielding bacterial growth compared with synovial membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their review work, Goh and Parvizi reported on the influence of antibiotics on the diagnosis of PJI [ 10 ]. The effect of prophylactic and therapeutic antibiotic administration on the diagnostic accuracy of microbiological cultures and serum or synovial biomarkers is presented.…”
mentioning
confidence: 99%